Investigation of the Effect of Seawater and Sulfate on the Properties of Cementitious Composites Containing Silica Fume - Şimşek, Osman; Aruntaş, H. Yılmaz; Demir, İlhami; Yaprak, Hasbi; Yazıcıoğlu, Salih (Springer Science and Business Media LLC, 2021)
Concrete consumes over two billion tons of freshwater every year and 75 % of regions of the world will become water shortages in 2050. Because of increasing freshwater scarcity seawater may become reasonable as an alternative mixing and curing water for concrete. In this study, seawater (SW) was utilized for mixing and curing of concrete and investigated the seawater and sulfate on the properties of cementitious composites containing silica fume (SF). Hence, SF was replaced with the cement at ratios corresponding to 0 %, 2.5 %, 5 %, 7.5 %, 10 %, 12.5 %, and 15 % by weight of cement, and SW and tap water (TW) were used as mixing water in the production of cementitious composites. Thus, the effect of SW on the properties of fresh cement pastes and the flexural and compressive strengths of 7-day, 28-day, and 90-day old cementitious composites were examined. Additionally, the lengthening change values of cementitious composites containing SF that were kept in 5 % Na2SO4 solution for 7-day, 28-day, and 90-day were determined. The SF delayed the setting period while increasing the water requirement of the cement paste. It is determined that the SW accelerated the setting period of cement. In the case when 10 % SF in cementitious composites was used, the maximum compressive and flexural strengths were obtained for cementitious composites produced by mixing with SW and SF fume at an age corresponding to 28-day and 90-day. It was observed that the length change of the cementitious composites decreased due to the increase in the SF replacement ratio.
Keywords: Cement paste; Cementitious composites; Silica fume; Seawater; Sulfate effect; 13. Climate action; 6. Clean water